PENGARUH TENAGA KERJA, TINGKAT UPAH DAN PENANAMAN MODAL TERHADAP PRODUK DOMESTIK REGIONAL BRUTO DI PROVINSI BALI - Umayanti, Ni Luh Made Sri Ayu; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 2 (2020): VOL 9 NO 2, FEBRUARI 2020 [ 233 - 472 ], 2020)
This study aims to determine (1) the effect of the number of workers on the GRDP of Bali Province; (2) the effect of wage level on GRDP in Bali Province; and (3) the influence of Domestic Investment (PMDN) on GRDP in Bali Province. The research method used in this study is descriptive quantitative. The data used is data that has been processed from the results of the National Labor Force Survey (SAKERNAS), as well as data from the Bali Province GRDP in the sector. These data are annual data released every year and obtained from the Central Bureau of Statistics of Bali Province. Meanwhile, for investment data obtained from BKPMD (Regional Investment Coordinating Board) Province of Bali. The data analysis method used in this study was multiple regression and classic assumption test consisting of normality test, multicolonearity test, autocorrelation test and heterocedasticity test. Based on the results of the study showed that (1) the number of workers, wage rates and domestic investment simultaneously had a positive effect on GRDP in Bali Province; (2) Labor, wage rates and domestic investment partially have a positive and significant effect on GRDP in the Province of Bali.